EDUCATIONAL CUSTOMER SATISFACTION - SOPIA, MAYA; DERMAWAN, OKI; JUNAIDAH, JUNAIDAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
In education, a marketing strategy is an effort to connect producers, usually schools, with customers or potential customers. The main goal of this strategy is to increase customer satisfaction by understanding customer needs and expectations and producing superior value compared to competitors. Schools must consider internal and external components and the environment that can influence the success of marketing plans. Education marketing helps attract new students and retain old students. Schools can manage and develop effective strategies by using the marketing mix concept (product, price, place, promotion, people, physical evidence, process). Building trust and loyalty also requires strengthening relationships with communities and maintaining educational quality. Educational institutions can adapt to changes and remain competitive in the market by using the right marketing strategies. This research analyzes the marketing strategies implemented by two private schools, SDIT Pelita Khoirul Ummah and SDIT Muhammadiyah Gunung Terang, in Bandar Lampung, in the context of Islamic education. Both schools have high standards in education and management, with professional teachers and adequate facilities. Although SDIT Pelita Khoirul Ummah shows a higher level of customer satisfaction in the tangible and responsiveness aspects, SDIT Muhammadiyah excels in reliability and assurance. Through a qualitative approach, this research reveals how the two schools strive to understand community needs and improve educational services in order to compete in a tight market. The research results show that effective marketing strategies contribute to parental trust and loyalty, as well as growth in student numbers. ABSTRAKDalam pendidikan, strategi pemasaran adalah upaya untuk menghubungkan produsen, biasanya sekolah, dengan pelanggan atau calon pelanggan. Tujuan utama dari strategi ini adalah untuk meningkatkan kepuasan pelanggan dengan memahami kebutuhan dan harapan pelanggan serta menghasilkan nilai yang lebih unggul dibandingkan dengan pesaing. Sekolah harus mempertimbangkan komponen internal dan eksternal serta lingkungan yang dapat mempengaruhi keberhasilan rencana pemasaran. Pemasaran pendidikan membantu menarik siswa baru dan mempertahankan siswa lama. Sekolah dapat mengelola dan mengembangkan strategi yang efektif dengan menggunakan konsep bauran pemasaran (produk, harga, tempat, promosi, orang, bukti fisik, proses). Membangun kepercayaan dan loyalitas juga memerlukan memperkuat hubungan dengan masyarakat dan mempertahankan kualitas pendidikan. Institusi pendidikan dapat menyesuaikan diri dengan perubahan dan tetap kompetitif di pasar dengan menggunakan strategi pemasaran yang tepat. Penelitian ini menganalisis strategi pemasaran yang diterapkan oleh dua sekolah swasta, SDIT Pelita Khoirul Ummah dan SDIT Muhammadiyah Gunung Terang, di Bandar Lampung, dalam konteks pendidikan Islam. Kedua sekolah memiliki standar tinggi dalam pendidikan dan manajemen, dengan pengajar yang profesional dan fasilitas yang memadai. Meskipun SDIT Pelita Khoirul Ummah menunjukkan tingkat kepuasan pelanggan yang lebih tinggi dalam aspek tangible dan responsiveness, SDIT Muhammadiyah unggul dalam reliability dan assurance. Melalui pendekatan kualitatif, penelitian ini mengungkap bagaimana kedua sekolah berupaya memahami kebutuhan masyarakat dan meningkatkan layanan pendidikan guna bersaing dalam pasar yang ketat. Hasil penelitian menunjukkan bahwa strategi pemasaran yang efektif berkontribusi pada kepercayaan dan loyalitas orang tua, serta pertumbuhan jumlah siswa.